22 July 2009 total solar eclipse induced gravity waves in ionosphere as inferred from GPS observations over EIA. Issue 9 (1st November 2016) - Kumar, K. Vijay; Maurya, Ajeet K.; Kumar, Sanjay; Singh, Rajesh
Abstract: In the present contribution we investigate the variation in the Global Positioning System (GPS) derived ionospheric Total Electron Content (TEC) over Equatorial Ionization Anomaly (EIA) region on the rare occasional astronomical phenomenon of total solar eclipse of 22 July 2009. The aim is to study and identify the wave like structure enumerated due to solar eclipse induced gravity waves in the F-region ionosphere altitude. The work is aimed to understand features of horizontal and vertical variation of atmospheric gravity waves (AGWs) properties over the Equatorial Ionization Anomaly (EIA) region in Indian low latitude region. The ionospheric observations is from the site of Allahabad (lat 25.4° N; lon. 81.9° E; dip 38.6° N) located at the fringe of eclipse totality path. The estimated vertical electron density profile from FORMOSAT-3/COSMIC GPS-RO satellite, considering all the satellite line of sight around the time of eclipse totality shows maximum depletion of 43%. The fast fourier transform and wavelet transform of GPS DTEC data from Allahabad station (Allahabad: lat 25.4 N; lon. 81.9 E) shows the presence of periodic waves of ∼20 to 45 min and ∼70 to 90 min period at F-region altitude. The shorter period correspond to the sunrise time morning terminator and longer period can be associated with solar eclipse generated AGWs. The most important result obtained is that our results along with previous result for wave like signatures in D-region ionosphere from Allahabad station show that AGWs generated by sunrise time terminator have similarity in the D and F region of the ionosphere but solar eclipse induced AGWs show higher period in the F-region compared to D-region ionosphere.